2022
DOI: 10.20448/jeelr.v9i1.3756
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Pandemic: Do Learning Motivation and Learning Self-Efficacy Exist among Higher Vocational College Students?

Abstract: COVID-19 first appeared in the first quarter of 2020 and spread rapidly throughout the world. Now, schools in China have resumed face-to-face teaching on campus, but the COVID-19 Pandemic still impacts normal teaching activities and student psychology. This quantitative research revealed the levels of learning motivation and learning self-efficacy among higher vocational college students. This study also investigated whether these variables vary according to students' gender, hometown, family structure and fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 11 publications
2
6
0
Order By: Relevance
“…In the same way, Tas et al found that most teachers believed that live classes contributed to meaningful student learning [15]. Tang and Osman's study showed that the COVID-19 pandemic did not affect student motivation, which is consistent with Belousova et al's findings, who noted that students were significantly more inclined to point to no change or increase in motivation in the distance format [29,30].…”
Section: Effectiveness Of Distance Education and Its Relations With M...supporting
confidence: 64%
“…In the same way, Tas et al found that most teachers believed that live classes contributed to meaningful student learning [15]. Tang and Osman's study showed that the COVID-19 pandemic did not affect student motivation, which is consistent with Belousova et al's findings, who noted that students were significantly more inclined to point to no change or increase in motivation in the distance format [29,30].…”
Section: Effectiveness Of Distance Education and Its Relations With M...supporting
confidence: 64%
“…Multiple studies [29,[92][93][94][95][96] have corroborated the positive correlation between general self-efficacy and critical thinking awareness. Research has also shown general self-efficacy can moderate other influencing factors of critical thinking awareness [97,98]. Overall, the above studies support a positive impact of general self-efficacy on critical thinking awareness.…”
Section: Research Hypothesissupporting
confidence: 53%
“…This confidence enables active analysis and critique of ideas rather than passive acceptance. Additionally, general self-efficacy is closely related to emotional states [96], as positive emotions enhance motivation [98]. Confident students tend to develop positive emotions, further motivating their participation, improving their understanding, and enhancing their critical thinking awareness.…”
Section: The Significant Impact Of General Self-efficacy On Learning ...mentioning
confidence: 99%
“…Carenys et al [11] acknowledged the influence of motivation on learning outcomes. Various studies support the impact that motivation has on behavior in fields such as academics [4,21,45,53], sports [12,16,23,39], teachers [27,43], also in the workplace [7,13], and with university students using various learning methodologies [3,10,22,31,37,40,41,44,55], in the teaching of English [15,19,35,61], and the results of learning [5,24,52,54], among others.…”
Section: Motivation As a Key Factor Of Microlearningmentioning
confidence: 99%